A National Survey of Chief Probation/Parole Officers' Perceived Interest in and Impact of Partnerships with Police. Issue 4 (2nd October 2017) - Matz, Adam K.; Kim, Bitna
ABSTRACT: Formal police–probation/parole partnerships grew in popularity in the 1990s, supported heavily by federal funding until the early 2000s. Using the membership list of the American Probation and Parole Association (APPA), this study represents the first attempt to survey a national sample of community supervision leaders concerning their interest, concerns, and perceived impact of partnerships with law enforcement. Few respondents indicated their agency was not already engaged in partnerships with police. However, the majority were informal, lacking clear interorganizational agreements, documentation, or evaluation outcomes. Results find the support of agency executives and supervisors is the most important variable in creating and maintaining viable and productive partnerships.